Brazil’s online politics: media effects on millennial’s voting intention and political involvement - Silva, Juliana Silveira e (2021)
Many of the traditional marketing concepts such as branding and stakeholders are now being applied into politics, increasing the usage of trending marketing practices such as social media (Keating & Melis, 2017; Nielsen, 2017; Parsons & Rowling, 2018). For millennials, online marketing is a part of their day to day life and some studies argue that this new communication channel is fundamental for parties, institutions and politicians who wish to target this generation (Parsons & Rowling, 2018; Towner & Munoz, 2016). Therefore, the purpose of this research is to understand to what extent does the usage of mass media or social media as source for political information and social media engagement will affect voting intention and political involvement among Brazilian millennials. A structured questionnaire was applied with a final sample of 51 elements, and data analysis was performed using t test and correlations to test the hypothesis presented. 4 of 5 hypotheses were accepted and suggest that social media has a great influence on Brazilian millennial’s voting intention and political involvement. It is therefore a fundamental tool to increase political participation among this generation.